2011
DOI: 10.1111/j.1537-2995.2011.03067.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of human parvovirus B19 DNA and antibodies in blood donors from four Chinese blood centers

Abstract: Whether B19 NAT screening of blood and blood products should be launched in China, larger studies are needed to facilitate an informed decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
37
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 47 publications
9
37
4
Order By: Relevance
“…This prevalence is also similar to the data obtained in the USA (0.88 %) [8]. Nevertheless, the observed prevalence was higher compared to countries like Belgium (0.2 %) [9] and China (0.58 %) [10] and lower compared to Dutch blood donors (2.5 %) [11]. Such a difference is probably due to the different sample volume used in the B19V testing, demographic characteristics of the populations or regional specifications of the B19V circulation (genotypes) in a given geographic region.…”
supporting
confidence: 77%
“…This prevalence is also similar to the data obtained in the USA (0.88 %) [8]. Nevertheless, the observed prevalence was higher compared to countries like Belgium (0.2 %) [9] and China (0.58 %) [10] and lower compared to Dutch blood donors (2.5 %) [11]. Such a difference is probably due to the different sample volume used in the B19V testing, demographic characteristics of the populations or regional specifications of the B19V circulation (genotypes) in a given geographic region.…”
supporting
confidence: 77%
“…The study indicated a 0.58% genome DNA prevalence rate among the blood donor population [26], but the study was not large enough to define range of viral titers, as samples with very high titers are relatively rare. In this study, we investigated B19V DNA contamination in 142 plasma pools from two Chinese manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…Hot-start amplification was performed under the following conditions: 1 cycle of 95°C for 10 min; 45 cycles of 95°C for 15 s, 60°C for 30 s, and 72°C for 30 s; and a final cycle of 95°C for 15 s, 60°C for 15 s, and then gradually increased to 95°C in 30 min at a ramp rate of 2%. Detailed Q-PCR procedures have been previously described [26]. Q-PCR detected B19V DNA positive samples were confirmed by nested PCR (nPCR) using the conserved primers located in the NS1 region described previously [25].…”
Section: Methodsmentioning
confidence: 99%
“…To measure the mRNA levels of HBV, Timp-1 , and Tgf-β1 , total RNA was isolated using a NucleoSpinRNA II kit (Macherey Nagal,GmbH & Co. KG, Germany) and reverse transcribed using a First Strand cDNA Synthesis Kit (Toyobo, Japan). All of the qPCR reactions were performed in triplicate in 96-well optical reaction plates using an ABI 7900 Sequence Detection System (Applied Biosystems, Foster City, CA) and SYBR Green I PCR mix (Roche Diagnostics, Indianapolis, IN) as previously described [31]. The primer sequences are shown in the S1 Table.…”
Section: Methodsmentioning
confidence: 99%